2022
DOI: 10.3390/en15051710
|View full text |Cite
|
Sign up to set email alerts
|

Energy Potential of Biogas Production in Ukraine

Abstract: Manufacturing and the further utilization of biogas is an efficient way of complementing or replacing primary energy resources. Ukraine has followed the global tendency to substitute fossil energy sources with renewable ones, which particularly includes biogas. Considering the experience of European countries, as well as the potential and needs of Ukraine, the necessity of biogas plant building implies three main factors: obtaining the energy sources, selling agricultural products and by-products of biogas pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…It can be seen that the educated workforce on average works in the tertiary or service sector because this sector requires an educated and skilled workforce. Meanwhile, workers whose education level is getting higher, the concentration of working in the primary sector is decreasing (Kucher et al, 2022). Therefore, the level of education in West Sumatra Province is still relatively low when viewed from the type of workforce.…”
Section: B Sector/ Employmentmentioning
confidence: 99%
“…It can be seen that the educated workforce on average works in the tertiary or service sector because this sector requires an educated and skilled workforce. Meanwhile, workers whose education level is getting higher, the concentration of working in the primary sector is decreasing (Kucher et al, 2022). Therefore, the level of education in West Sumatra Province is still relatively low when viewed from the type of workforce.…”
Section: B Sector/ Employmentmentioning
confidence: 99%
“…According to empirical studies on the importance of biogas, animal and agricultural wastes are used to produce a large amount of biogas , notably in nations such as India, Greece, China, and Ukraine (Talevi et al, 2022;Aravani et al, 2022;Kucher et al, 2022). A recent study by Ahmed et al (2022) indicated that placentas have the same biogas potential as other organic wastes in renewable energy production.…”
Section: Ef (Gha) Percentmentioning
confidence: 99%
“…Sources of pollution can be harmful substances introduced into the soil, noncompliance with crop rotations, use of heavy machinery that destroys the soil structure, and irrational use of resources, an imbalance of foraging, animal and plant diseases, and more. However, it should be noted that the potential of agricultural enterprises differs due to differences in geographical location, natural and climatic conditions, and the level of the availability of biological resources and opportunities for their continuous quality improvement [23][24][25][26][27][28].…”
Section: Reorientation Of Understanding the Economic Essence Of Econo...mentioning
confidence: 99%
“…Ukraine has several models of selling environmental certificates, forecast estimates of which confirm the effectiveness of this tool for the development of the agricultural sector as a whole, as well as direct and sustainable financial benefits and opportunities for farmers. In addition, today's carbon market is promising globally, which means that prices will rise significantly [11,16,28].…”
Section: Adaptive Reorientation Of the Agricultural Sector As A Tool ...mentioning
confidence: 99%